Internal Finance and Growth: Comparison Between Firms in Indonesia and Bangladesh - Husain, Humaira (International Journal of Economics and Financial Issues, 2015)
This paper investigates a panel of 289 Indonesian firms and 73 Bangladeshi firms over the period 1998-2006 to study the extent to which the availability of the Internal finance in terms of cash-flow influences firms' growth. There is less than one for one correspondence between assets growth and Internal Finance using the simple dynamic asset growth model augmented with cash-flow. This result is robust to estimating more general and extended dynamic model. Growth of assets is not constrained by the profit generating capacity of firms in Indonesia as well as in Bangladesh. Along with internally generated funds, growth of firms is determined by external equity finance, as well as institutional finance. Keywords: Assets Growth, Cash-flow, Equity Finance JEL Classification: D92